2021
DOI: 10.1101/2021.03.24.436801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of ventral subiculum neuronal ensembles in incubation of oxycodone craving after electric barrier-induced voluntary abstinence

Abstract: We recently developed a rat model of incubation of oxycodone craving where opioid seeking progressively increases after voluntary suppression of drug self-administration by adverse consequences of drug seeking. Here, we studied the role of ventral subiculum (vSub) neuronal ensembles in this incubation, using the activity marker Fos, muscimol-baclofen (GABAergic agonists) inactivation, and Daun02 chemogenetic inactivation.We trained Sprague-Dawley or Fos-lacZ transgenic male and female rats to self-administer o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Evidence from recent studies suggests that this is also the case for voluntary abstinence relapse models. Thus, inhibition of vSub decreases both context-induced relapse to alcohol seeking after punishment and incubation of opioid seeking after electric barrier-induced abstinence Fredriksson et al, 2021). Additionally, inhibition of AI decreases relapse to both fentanyl and methamphetamine seeking after food choice-induced abstinence (Venniro et al, 2017a;Reiner et al, 2020).…”
Section: B Similarities and Differences Of Drug Classes Within Volunt...mentioning
confidence: 97%
See 2 more Smart Citations
“…Evidence from recent studies suggests that this is also the case for voluntary abstinence relapse models. Thus, inhibition of vSub decreases both context-induced relapse to alcohol seeking after punishment and incubation of opioid seeking after electric barrier-induced abstinence Fredriksson et al, 2021). Additionally, inhibition of AI decreases relapse to both fentanyl and methamphetamine seeking after food choice-induced abstinence (Venniro et al, 2017a;Reiner et al, 2020).…”
Section: B Similarities and Differences Of Drug Classes Within Volunt...mentioning
confidence: 97%
“…In another study, Fredriksson et al (2021) determined the role of vSub in incubation of oxycodone seeking after electric barrier-induced abstinence in male and female rats. They tested the rats for relapse to oxycodone seeking on abstinence day 15 and extracted their brains for Fos immunohistochemistry or tested the rats after vSub injections of vehicle or muscimol 1 baclofen on abstinence day 1 or day 15 after forced or electric barrier-induced abstinence.…”
Section: Fredriksson Et Al (2020) Modified the Electric Barrier-relap...mentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, we found no age differences in oxycodone selfadministration in rats at a dose of 0.1 mg/kg under extended access condition (6 h/day). We chose this experimental condition based on previous studies from us and others detecting reliable oxycodone self-administration and incubation of oxycodone craving in adult rats (Fredriksson et al, 2020(Fredriksson et al, , 2021Altshuler et al, 2021). In contrast, an early dose-response study showed that adolescent mice self-administered less oxycodone than adult mice across various doses (Zhang et al, 2009).…”
Section: Incubation Of Drug Craving Following Adolescent-onset Drug Self-administrationmentioning
confidence: 99%
“…One of the main barriers to addressing this opioid epidemic is the prevalence of relapse to drug use ( Gostin et al, 2017 ; Kariisa et al, 2019 ), often triggered by re-exposure to drug-associated cues ( O’Brien et al, 1986 ). Recently, we and others demonstrated that oxycodone seeking in adult rats progressively increases after abstinence from oxycodone self-administration ( Fredriksson et al, 2020 , 2021 ; Altshuler et al, 2021 ). This incubation of craving phenomenon has also been previously observed in rats with a history of cocaine ( Grimm et al, 2001 ), heroin ( Shalev et al, 2001 ), nicotine ( Abdolahi et al, 2010 ), alcohol ( Bienkowski et al, 2004 ), methamphetamine ( Shepard et al, 2004 ), and sucrose ( Grimm et al, 2005 ) self-administration.…”
Section: Introductionmentioning
confidence: 99%